(3JMQjQ cJGH eCNhPGJ GQTejOSs - (3GQTejOSs
(3ChdgG (B:s
(3HYO GdOjHGLI ajgG CTcGd MSfI bdjdI GdYOO cKjQI GdahGFO aj CUhd GdgfOSI aj ZGjI GdLhOI s
(3Vef eLehY , JQJjHgG (B: 13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(1760) s
Keywords: (3eJaQbGJs